Front Cover: Magnetically Manipulable Ionic Liquid Crystals Incorporating Neutral Radical Moiety (ChemPlusChem 3/2022). Issue 3 (3rd February 2022) - Uchida, Yoshiaki; Sakaguchi, Tatsunori; Oki, Shigeaki; Shimono, Satoshi; Park, Jayeong; Sugiyama, Masahito; Sato, Shuichi; Zaytseva, Elena; Mazhukin, Dmitrii G.; Tamura, Rui
Abstract : The front cover displays novel ionic liquid crystalline (ILC) compounds containing a nitroxide radical unit in the organic cations, showing an enantiotropic smectic A (SmA) phase. One of the ILC compounds shows strong intermolecular magnetic interactions owing to the nanosegregation of strongly bonded ionic and non‐ionic moieties. Its droplet can be magnetically manipulable. More information can be found in the Full Paper by Yoshiaki Uchida, Rui Tamura, and co‐workers .